Express `y` from the first equation: `y=5-3/2 x.` Substitute it into the second equation and obtain

`2x+5(5-3/2 x)=3,` or

`-11/2 x=-22.`

So `x=4` and `y=5-3/2 x=5-6=-1.`

The answer: `x=4,` `y=-1.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now